Who knew? responsibility without awareness - Sher, George (New York ; Oxford : Oxford University Press, 2009)
Unlike most other discussion of responsibility, which focus on the idea that to be responsible, agents must in some sense act voluntarily, this book focuses on the relatively neglected idea that they must in some sense know what they are doing.
Description based on print version record.
Includes index.
Keywords: Responsibility; Awareness